Circum-Saharan Prehistory through the Lens of mtDNA Diversity - Diallo, Mame Yoro; Čížková, Martina; Kulichová, Iva; Podgorná, Eliška; Priehodová, Edita; Nováčková, Jana; Fernandes, Veronica; Pereira, Luísa; Černý, Viktor (Genes, 2022)
African history has been significantly influenced by the Sahara, which has represented a barrier for migrations of all living beings, including humans. Major exceptions were the gene flow events that took place between North African and sub-Saharan populations during the so-called African Humid Periods, especially in the Early Holocene (11.5 to 5.5 thousand years ago), and more recently in connection with trans-Saharan commercial routes. In this study, we describe mitochondrial DNA (mtDNA) diversity of human populations from both sides of the Sahara Desert, i.e., both from North Africa and the Sahel/Savannah belt. The final dataset of 7213 mtDNA sequences from 134 African populations encompasses 470 newly collected and 6743 previously published samples, which were analyzed using descriptive methods and Bayesian statistics. We completely sequenced 26 mtDNAs from sub-Saharan samples belonging to the Eurasian haplogroup N1. Analyses of these N1 mitogenomes revealed their possible routes to the Sahel, mostly via Bab el-Mandab. Our results indicate that maternal gene flow must have been important in this circum-Saharan space, not only within North Africa and the Sahel/Savannah belt but also between these two regions.
Keywords: Bayesova věta; severní Afrika; DNA, Mitochondrial; Gene Flow; Black People; černoši; Africa, Northern; Humans; population history; tok genů; lidé; mtDNA diversity; North Africa; Bayes Theorem; mitochondriální DNA; Sahel/Savannah belt